Language Processing in EFL Learners: A Psycholinguistic Study of Lexical Access and Sentence Comprehension - Zahwa Nazhifah Limbeng; Khairun Nisa; Faris Fadillah; Yani Lubis (Asosiasi Dosen Muda Indonesia, 2026)
This study investigates language processing in EFL learners from a psycholinguistic perspective, with a focus on lexical access and sentence comprehension. Many EFL learners experience persistent comprehension difficulties despite years of formal instruction. This study aims to explain these difficulties by examining underlying cognitive processes rather than surface-level performance. The research employed a qualitative design involving undergraduate EFL students. Data were collected through think-aloud protocols, semi-structured interviews, reading comprehension tasks, and field notes. The analysis applied thematic procedures to identify patterns related to word retrieval, processing strategies, and sentence parsing. The findings reveal five dominant issues: delayed lexical access, reliance on word-by-word processing, difficulty with complex sentence structures, heavy dependence on first-language translation, and low automaticity in language processing. These factors interacted to increase cognitive load and disrupt real-time comprehension. The results indicate that comprehension failure stems primarily from processing constraints rather than insufficient grammatical knowledge. The study highlights the importance of incorporating psycholinguistic principles into EFL instruction. Teaching practices should prioritize processing efficiency, repeated exposure, and incremental sentence comprehension. By aligning pedagogy with how learners process language cognitively, EFL instruction can become more effective and sustainable.